АНИЗОТРОПИЯ ДЕФОРМАТИВНЫХ СВОЙСТВ КОМПОЗИТНЫХ МАТЕРИАЛОВ ПРИ РАЗЛИЧНЫХ СЛУЧАЯХ ЦИКЛИЧЕСКОГО НАГРУЖЕНИЯ - Н. Е. Саркисян; Н. Н. Саркисян; А. Н. Казарян (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Investigated changing of deformability anisotropia of fiberglass, black-reinforced and organic plastics under pulsating cycle of straining and trapeziform cycle straining-relaxation. Analyzed the impact of persistent loading frequency and loading time into material under the constant loading and conventional relaxation. Established the stability of fiberglass, black-reinforced plastics deformation under straining with grain. The growth of deformation in time depending to loading frequency, strain level and angel orientation depending to fiber are taking place.
Keywords: Mechanics of deformable solids; Generalities, axiomatics, foundations of continuum mechanics of solids